SELECTION OF CRITERIA FOR ASSESSING THE EFFECTIVENESS OF RENEWABLE ENERGY SUPPORT POLICIES - N.А. Riazanova (Економіка та право, 2018)
At the moment, Ukraine has set targets for expanding the use of renewable energy sources (RES), while one of the key tasks is to substantiate and accurately assess the economic efficiency of using RES with the use of various criteria and indicators. The purpose of the article is to research and develop scientific and economic decisions on the assessment of the efficiency of the use of renewable energy sources, and to justify the selection of criteria for assessing renewable energy support policies. Renewable energy policy is a matter of ongoing assessment, because it implies significant financial support that should be monitored continuously and thoroughly. The article highlights five criteria for assessing renewable energy support policies: efficiency, efficiency, equity, institutional feasibility, reproducibility (long-term functioning). The article substantiates the choice of criteria for assessing the effectiveness of the policy of supporting renewable energy sources, namely the criterion of economic efficiency, which includes static and dynamic efficiency. Effectiveness shows the ratio of realizing the goals of developing RES to the cost of resources that have been spent to achieve these goals. The article presents the calculation and justification of the use of indemnification indicators that characterize the criterion of economic efficiency. The criterion of justice and its estimation are analyzed. Comparison of the use of the provided indicators of political support for renewable energy sources has been com pared. The parameters of dependence of dynamic efficiency are determined. Advantages of RES technologies relative to traditional generation depend to a large extent on local conditions: where there are favorable conditions for implementation of RES technologies, it is possible to achieve lower generation costs based on RES, rather than fossil fuels. In most cases, generation costs based on RES are higher than in traditional generation. Over time, these costs will fall, but by the time that renewable energy reaches the parity with traditional generation, the state will have to bear additional support for the industry with appropriate political support using a variety of criteria with the appropriate set of indicators.